Evolution of soil arching; 2D DEM simulations. (March 2016) - Rui, Rui; van Tol, Frits; Xia, Xiao-Long; van Eekelen, Suzanne; Hu, Gang; Xia, Yuan-you
Abstract: A series of model tests were performed using a 2D multiple trapdoor system, similar to a 2D unreinforced piled embankment. Three soil arching evolution patterns were observed in the tests: the triangular expanding pattern, the tower-shaped evolution pattern, and the equal settlement pattern. The model tests were simulated using the discrete element method (DEM), and the micromechanical parameters were calibrated using the stress–strain curves from plane strain compression tests. Noncircular particle clumps were adopted to achieve a high frictional behavior of the sand. The calculated deformation and stress distribution well-matched the results of the model tests. The three evolution patterns were observed in the DEM simulations, and additional calculations were performed to specify the application conditions. The DEM simulations showed that the contact forces between the particles formed a strong force chain network enveloping the triangular and tower-shaped deformation regions. Another, much weaker, force chain within the deformation region supported the strong force chain outside.